Involvement and Multicultural Counselling Competency Among School Guidance and Counselling Teacher Towards Special Needs Students - Norafifah Bali; Mohamad Hashim Othman (Asian Social Work Journal, 2017)
chool Guidance and Counselling Teachers who involved in the Integrated Special Education Program and the Inclusive Education Program are facing unique challenges. This unique challenge is due to their responsibility in providing guidance and counselling services to two groups of client, the mainstream students and the Special Needs Students. Previous study found that School Guidance and Counselling Teachers were less involved in providing guidance and counselling services to Special Needs Students and their counseling competence towards Special Needs Students level was indicated from low to moderate. Therefore, further studies on involvement and competencies need to be implemented. A qualitative research methodology such as Multiple Case Studies is the ideal research design for this study. There are two proposed methods of data collection, semi structured interviews and document analysis. The results of this study will contribute to the Multicultural Counselling Model in the Special Education setting and the improvement of the guideline of guidance and counselling